The Effectiveness of E-Government Services in Enhancing Public Trust: A Comparative Study Across ASEAN Countries - Ramadhani, Ditya Putri Safira; Sulaiman, Haikal Rahmat; Anggraeni, Andita Wulan; Aisyah, Siti (Journal of Management and Informatics, 2025)
The implementation of e-government has become a key strategy for enhancing public trust in government institutions, particularly in ASEAN countries with varying levels of digital transformation. However, the extent to which e-government adoption influences public trust remains unclear due to disparities in digital infrastructure, public engagement, and policy frameworks. This study examines the relationship between e-government implementation and public trust in ASEAN, identifying key influencing factors. This research employs a quantitative approach using panel data analysis of e-government indices and public trust levels from 2015 to 2023. The dataset includes ten ASEAN countries, covering variables such as the E-Government Development Index (EGDI), digital participation rates, and GDP per capita. The results indicate a significant positive correlation (r = 0.78, p < 0.01) between e-government adoption and public trust, with countries having higher digital participation rates (above 60%) experiencing greater trust improvements. Furthermore, transparency and service reliability (β = 0.64) are more influential than economic factors such as GDP per capita (β = 0.32) in shaping public trust. These findings highlight the crucial role of digital service quality and citizen engagement in fostering public trust beyond economic growth. This study contributes to the literature by emphasizing the need to strengthen digital infrastructure and public participation in e-government initiatives. Future research should explore the socio-political aspects of e-government adoption to provide a deeper understanding of its long-term impact on governance.